TOPOGRAPHICALLY INDUCED TURBULENCE ON CONTINENTAL SHELF OFF JOGASHIMA, SAGAMI BAY, JAPAN - Yuli Naulita (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
ABSTRACT Direct turbulence measurements using TurboMAP over a “small ridge” on the continental shelf off Jogashima, Sagami Bay, Japan revealed an active layer of topographically induced turbulence. The active layer ( = 10-7 - 10-6 W kg-1) located at mid-depth of 200 – 250 m, occurred on alternate side of “small ridge” depending on the direction of the tidal current. This active layer was accompanied by rebounded-isopycnal surfaces 26.0 - 26.1 σθ , in which all in qualitative manner showed an internal hydraulic flow control on the shelf. The turbulence friction velocity was two order of magnitude lower than observed- in this active layer explaining a less role of bottom friction than hydraulic flow to the high turbulence layer. Keywords: topographically induced turbulence, continental shelf, internal hydraulic flow